National literary history writing in İsmail Habib Sevük’s Türk teceddüd edebiyatı tarihi - Sevinç, Zeynep Hazal. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis focuses on İsmail Habib Sevük’s Türk Teceddüd Edebiyatı Tarihi and examines this work through the conceptualization of national literary historiography. By revealing the relationship between nation building and literature, it shows the connection between the establishment of the nation state and the emergence of modern literary historiography. This work exerts that in line with a nationalist ideology, Sevük constructed a narrative and teleological literary historiography based on a national model. He tries to show the parallelism between the historical adventure of a homogenous Turkish nation and the development of its literature. This thesis shows that Sevük builds a literary history narrative which progresses linearly towards the goal of national literature by basing the origins of Turkish literature on a very old and ambiguous Turkish past. In the adventure of national literary history, while folk literature is glorified, divan literature, which is considered Ottoman literature, is eliminated. The new literature which is at the center of the work, forms the literary reflection of the changes and transformations that started with the Tanzimat on the path of modernization and nationalization. This thesis also claims that the Tanzimat and Servet-i Fünun Periods are also positioned according to a national ideal of literature. As to the last period, which is called national movement literature, is the aim and final point of both the whole Turkish literature and the new literature.
Keywords: Turkish literature -- History and criticism.